AFLES STRENGTHENS NETWORKING AND COLLABORATION AMONG ASEAN POSTGRADUATE STUDENTS - MPRC, Pusat Media & Perhubungan Awam (USM, 2015)
NILAI, NEGERI SEMBILAN, 24 July 2015 The development and progress of higher education in ASEAN countries could be further strengthened through the organisation of the ASEAN Future Leaders Summit 2015 (AFLES 2015), said the Deputy Minister of Education II, P. Kamalanathan P. Panchanathan.